Total synthesis and biological evaluation of fluorinated cryptophycins - Weiß, Christine; Bogner, Tobias; Sammet, Benedikt; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2012)
Cryptophycins are cytotoxic natural products that exhibit considerable activities even against multi-drug-resistant tumor cell lines. As fluorinated pharmaceuticals have become more and more important during the past decades, fluorine-functionalized cryptophycins were synthesized and evaluated in cell-based cytotoxicity assays. The unit A trifluoromethyl-modified cryptophycin proved to be highly active against KB-3-1 cells and exhibited an IC50 value in the low picomolar range. However, the replacement of the 3-chloro-4-methoxyphenyl-substituent in unit B by a pentafluorophenyl moiety resulted in a significant loss of activity.
Keywords: antimitotic drug; cytotoxicity; depsipeptide; fluorinated natural product analogues; structure-activity relationship